2018
DOI: 10.5223/pghn.2018.21.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Study of Acute Gastroenteritis Etiologies in Hospitalized Children in South Lebanon (SAGE study)

Abstract: PurposeAcute gastroenteritis (AGE) is a major cause of morbidity and remains a major cause of hospitalization. Following the Syrian refugee crisis and insufficient clean water in the region, this study reviews the etiological and epidemiological data in Lebanon.MethodsWe prospectively analyzed demographic, clinical and routine laboratory data of 198 children from the age of 1 month to 10 years old who were admitted with the diagnosis of AGE to a private tertiary care hospital located in the district of Nabatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
6
16
1
Order By: Relevance
“…Rotavirus mainly spread through contact with infected persons, contaminated environmental surfaces or via ingestion of contaminated food and water. 23.08% of the children in our study showed mixed infection mostly were parasitic and bacterial while unidentified group was 55.62% which was quite higher than the study by Ghssein G et al [16] . Who reported it as 42.4%.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Rotavirus mainly spread through contact with infected persons, contaminated environmental surfaces or via ingestion of contaminated food and water. 23.08% of the children in our study showed mixed infection mostly were parasitic and bacterial while unidentified group was 55.62% which was quite higher than the study by Ghssein G et al [16] . Who reported it as 42.4%.…”
Section: Discussioncontrasting
confidence: 59%
“…In other study by Gebreegziabher G et al the overall prevalence of Salmonella species was 7.3% and 6.9% Shigella species were isolated from children with diarrhoea [15] . Rotaviral infections found in our study was 23.08% it was 19 % in a study by Ghssein G et al [16] . Many studies have reported rotavirus is a leading cause of paediatric AGE, accounting for 27-51% of all diarrheal cases in children less than 5 years of age [17] .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A recent study performed by our team in South Lebanon evaluated common causes of AGE among hospitalized children during the period of summer 2014. Results from this study indicated that 40.4% of all hospitalized cases in children were due to AGE, with rotavirus and E. histolytica being the major identified disease-causing pathogens [20]. To widen our knowledge regarding the incidence, age distribution, etiologies, AGE incidence throughout the different months of the year for each pathogen involved, protective factors, and correlation between AGE causes and severity of the disease among hospitalized children in Southern Lebanon, we performed this current study with a larger sample size, to cover most of the South district.…”
Section: Introductionmentioning
confidence: 99%
“…The use of new technologies has strengthened diagnostic systems, leading to identifying other viral agents present in feces that were not previously identified (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%